Mycobacterium tuberculosis-macrophage interaction: Molecular updates - Bo, Haotian; Moure, Ulrich Aymard Ekomi; Yang, Yuanmiao; Pan, Jun; Li, Li; Wang, Miao; Ke, Xiaoxue; Cui, Hongjuan (Frontiers in Cellular and Infection Microbiology, 2023)
Mycobacterium tuberculosis (Mtb), the causative agent of Tuberculosis (TB), remains a pathogen of great interest on a global scale. This obligate intracellular airborne pathogen specifically affects the lungs, where it first interacts with resident macrophages. Host macrophage intracellular environment is very hostile to foreign bodies to survive, including acidic pH, oxidative and nitrosative stresses, and nutrient deprivation. Although the redoubtable and powerful killing ability of these immune cells, Mtb is well-known to subvert the host immune system and create the infection due to its particular and potential genetic arsenal and related secreted effector proteins. A panel of in vivo and in vitro studies have explored Mtb-host macrophage interactions and reported several aspects of this crosstalk. As far as we know, this crosstalk undoubtedly represents a determinant step in Mtb infection in the sense that not only lung macrophages are the primary immune cells encountered by Mtb in the host, but also, in the fact that they have a strong influence on Mtb infection fate. In this review, we sum up Mtb effector molecules that interact with the macrophage throughout this crosstalk. Besides, we report and discuss recent and previously unknown mechanisms by which macrophages control and eliminate Mtb as well as how Mtb manipulates host contents for its benefits. A depth understanding of these mechanisms is of great significance in TB prevention, diagnosis, and treatment.